Who speaks for the future of Earth? How critical social science can extend the conversation on the Anthropocene. (May 2015) - Lövbrand, Eva; Beck, Silke; Chilvers, Jason; Forsyth, Tim; Hedrén, Johan; Hulme, Mike; Lidskog, Rolf; Vasileiadou, Eleftheria
Highlights: The Anthropocene is an unsettled concept. The dominant interpretation naturalizes nature and downplays social diversity. Solutions-oriented research restricts the conversation on the future of Earth. Critical and interpretative social science may re-politicize the Anthropocene. Abstract: This paper asks how the social sciences can engage with the idea of the Anthropocene in productive ways. In response to this question we outline an interpretative research agenda that allows critical engagement with the Anthropocene as a socially and culturally bounded object with many possible meanings and political trajectories. In order to facilitate the kind of political mobilization required to meet the complex environmental challenges of our times, we argue that the social sciences should refrain from adjusting to standardized research agendas and templates. A more urgent analytical challenge lies in exposing, challenging and extending the ontological assumptions that inform how we make sense of and respond to a rapidly changing environment. By cultivating environmental research that opens up multiple interpretations of the Anthropocene, the social sciences can help to extend the realm of the possible for environmental politics.